Pearls and pitfalls of cuffless blood pressure monitoring devices - Radu-Alexandru Iacobescu; Bogdan-Danut Florescu; Alina-Mihaela Dimache; Luiza-Elena Corneanu; Elena Adorata Coman (Romanian Medical Journal, 2023)
Cuffless blood pressure measuring devices are emerging as alternatives for out-of-office assessment of patients with hypertension. This novel technology promises to deliver continuous or beat-to-beat blood pressure measurement and resolve some of the inconveniences associated with conventional cuff-based devices such as improper cuff fit, discomfort, low adherence to monitoring, and technical challenges. Blood pressure can be estimated based on phenomena related to cardiovascular activity: pulse wave velocity, pulse wave analysis, tonometry, and volume clamping. In this narrative review, we seek to summarize current approaches for nontraditional measurement of blood pressure and discuss some of the benefits and limitations of this technology.